Catalytic effects of inherent alkali and alkaline earth metallic species on steam gasification of biomass. (7th December 2015) - Jiang, Long; Hu, Song; Wang, Yi; Su, Sheng; Sun, Lushi; Xu, Boyang; He, Limo; Xiang, Jun
Abstract: This study aimed to understand the mechanism of dual catalytic effects of inherent alkali and alkaline earth metallic species (AAEMs) on biomass gasification. Two kinds of typical Chinese agricultural biomass were gasified using updraft quartz reactor with steam. The results indicated that external steam had negligible effects on promoting further thermal cracking or reforming of tar under 900 °C. The presence of AAEMs enhanced the production of H2 and CO2, while inhibited the production of CO、CH4 、C2 H4 and C2 H6 . The heterogeneous char-steam reaction, as well as the homogeneous hydrocarbons reforming and water-gas shift reactions were promoted by the presence of AAEMs. Alkaline earth metals had more significant catalytic effects on water-gas shift reaction compared to alkali metals. The results from UV fluorescence spectra further proved that the additional steam had negligible promoting effects on secondary reforming of tar, while the inherent AAEMs had a significant catalytic role in thermal cracking and reforming of tars. Graphical abstract: The dual catalytic effects of inherent AAEMs on steam gasification of biomass can be illustrated by the figure. Part of AAEMs volatilized into gaseous phase, involving in homogeneous reforming reactions such as volatile-volatile and volatile-gasification agent reactions, and the other part of AAEMs remained in bio-char, involving in heterogeneous reactions such as char-gasification agent and char-volatile reactions, which would alter reaction pathway of biomass gasification. Highlights: External steam had negligible effects on promoting further thermal cracking of tar. Inherent AAEMs had significant catalytic roles in thermal cracking/reforming of tar. The presence of AAEMs enhanced the production of H2 and CO2 . The presence of AAEMs inhibited the production of CO、CH4 、C2 H4 and C2 H6 .